A cidade e o cinema [negro]: o caso FESPACO - Oliveira, Maíra Zenun Almada de (2019)
This PhD thesis entitled The City and the [Black] Cinema: the FESPACO’s case, it is the result of an writexperience [auto] ethnographic in which I set out to meet one of the largest African film festivals, the FESPACO – Panafrican Film and Television Festival of Ouagadougou – which takes place in Burkina Faso, a country located in West Africa from 1969 to the present day. The work therefore brings the result of this case study and is divided into three parts, respectively: the first on the host city of the ritual, the capital-Ouagadougou; the second about the art of cinema makes (in)visible certain [black] bodies; and the third, properly, about FESPACO, in relation to what was previously presented. In each of these stages of the text, I tried to establish and discuss the possible links between the socio-political and spatial conjuncture that hosts the festival, in relation to this kind of cinema that calls itself (or is called) black. All of this, having as its main reference and starting point my own life experience and place of speech, given the complexity of what was generated from European colonialism. In this sense, in theoretical and methodological terms, and in order to also arouse a discussion about art and society, such writexperience was carried out with the objective of understanding the festival in the light of questions concerning the erasures and the (in)visibilities promoted by knowledge and (in) your production networks.